Time-dependent buckling delamination of thin plastic films and their conformability: Observations and modeling. (May 2020) - Zhang, Haiying; Zhou, Zhenwen; Chudnovsky, Alexander; Pham, Hoang
Abstract: Conformability is a property of materials that allows them to conform to the contours of a curved or rough surface. The lack of conformability of a thin plastic film lying on a non-flat substrate is commonly manifested in formation of blisters, wrinkles and other forms of delamination. The delamination is driven by elastic energy of thin film associated with the film deformation required by film application. A simple method of observation and quantitative characterization of delamination and its evolution in time is proposed. The time dependency of delamination is driven by an interplay between the stress relaxation within the film and viscous flow of adhesive. Thus, the conformability of multilayer system is controlled by the stiffness and relaxation characteristics of the film as well as the time dependent strength of adhesive. A methodology of testing the conformability and measurements of delamination growth, as well as quantitative modeling of the process are presented.